India's economic reforms and development - Vaidyanathan, A. (New Delhi : Academic Foundation, 2003)
The essays in this collection provide an overview of evolution of this process culminating in the far-reaching orientation strategy and policies during the nineties and a critical assessment of their rationale, implementation and impact from the political economy perspective.
Includes bibliographical references.
osc 12/07/16
Loans
Keywords: Structural adjustment (Economic policy); India; India